2016
DOI: 10.1002/2015rs005933
|View full text |Cite
|
Sign up to set email alerts
|

Performance of ionospheric maps in support of long baseline GNSS kinematic positioning at low latitudes

Abstract: Ionospheric scintillation occurs mainly at high and low latitude regions of the Earth and may impose serious degradation on GNSS (Global Navigation Satellite System) functionality. The Brazilian territory sits on one of the most affected areas of the globe, where the ionosphere behaves very unpredictably, with strong scintillation frequently occurring in the local postsunset hours. The correlation between scintillation occurrence and sharp variations in the ionospheric total electron content (TEC) in Brazil is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Another approach, mainly applied in post-processing applications, utilizes GNSS-based global ionospheric maps (Zhang et al 2016). These maps, however, feature insufficient spatio-temporal resolution to capture the disturbances during high ionospheric activity (Park et al 2016). Analyzing the other possibilities it should be noted that the benefit from the application of ionosphere-free linear combination does not offset the drawback of providing a float-only solution.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach, mainly applied in post-processing applications, utilizes GNSS-based global ionospheric maps (Zhang et al 2016). These maps, however, feature insufficient spatio-temporal resolution to capture the disturbances during high ionospheric activity (Park et al 2016). Analyzing the other possibilities it should be noted that the benefit from the application of ionosphere-free linear combination does not offset the drawback of providing a float-only solution.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed forecasting technique can be of interest for implementing real‐time mitigation algorithms of the ionospheric effect on GNSS precise positioning techniques, faced by mitigating scintillation. In Park et al (), an off‐line application of the proposed technique has been tested in long baseline RTK positioning over Brazil. The investigation has shown that TEC map obtained by applying this regional empirical model provides, on the average and under strong scintillation, an improvement of 40.4% over the GIM TEC map in terms of positioning accuracy for the kinematic positioning performance.…”
Section: Discussionmentioning
confidence: 99%
“…Radio Science thin shell at an altitude of 350. The thin shell approximation has been chosen since it guarantees a fast computation and a quite accurate description of the ionosphere from a positioning point of view (Park et al, 2016(Park et al, , 2017.…”
Section: 1029/2017rs006310mentioning
confidence: 99%
See 1 more Smart Citation
“…Development of proper ionospheric forecasting solutions further complicates not only because helio-geophysical disturbances alter the "regular" properties and dynamics of the ionospheric plasma, but also because the users demanding for their implementation in real-time to support a variety of needs, e.g. for mitigating the ionospheric effects of space weather on modern technological infrastructures relying on space-based navigation systems (Cesaroni et al, 2015;Park et al, 2016). Accordingly, efforts are continuously devoted to upgrade the so-called "climatological models", able to provide median features of, e.g., the ionospheric electron density profile, to the real-time weather predictions.…”
Section: Introductionmentioning
confidence: 99%